(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Nowadays, in almost all fields, analysis of relation between Job Satisfaction and Emotional Intelligence has been one of the most crucial research subjects to get high productivity. These two are the main concepts in modern work environment. This paper aims at studying relationship between Job Satisfaction and Emotional Intelligence. For this reason, 50 managers of Government Banks were chosen (random stratified sample) and the data was gathered by running Sibria Shiring Emotional Intelligence Questionnaire and Bray field & Rothe Job Satisfaction Questionnaire. After that, to analyze the data, Pearson correlation analysis was done. Results showed that there is a relation between Emotional Intelligence and Job Satisfaction. The relation between job satisfaction and each of the emotional intelligence criteria (self-awareness, self-control, self motivation, Intimacy and social skills) were upheld. The analysis gave a positive relation between two variables. This study will help various researchers and practitioners in realising the link between these two variables.